On the Theodoxus prevostianus (C. Pfeiffer, 1828) population of the Tükör Spring in Kács (Hungary) - Sándor Ötvös; János Varga (Historia naturalis bulgarica, 2023)
For the past nearly 15 years, we have been conducting freshwater malacological studies in the Kács spring area, a wetland of great importance in the South-Eastern Bükk (Hungary). The focus of our research is the species Theodoxus prevostianus (C. Pfeiffer, 1828). In the present study, population density records from the direct outlet of the tepidwater Tükör Spring are presented and compared. At the study site, the number of individuals of the accompanying malacofauna of the species under study was also recorded (Microcolpia daudebartii (Prevost, 1821), Bythinella thermophila Glöer, Varga et Mrkvicka, 2015, Bythinella pannonica (Frauenfeld, 1865). The data were recorded in 2006 (general survey), 2010 (drastic reduction) and 2021 (relocation). On the stone slab squares used to record individual counts, we detected a high-density population in 2006, a drastically reduced population in 2010 and a high-density population again in 2021.